2019
DOI: 10.1021/acs.joc.9b00320
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Functionalized Glutarimide Using Oxidative N-Heterocyclic Carbene Catalysis: A Formal Synthesis of (−)-Paroxetine

Abstract: A simple yet highly effective approach toward enantioselective synthesis of trans-3,4-disubstituted glutarimides from readily available starting materials is developed using oxidative N-heterocyclic carbene catalysis. The catalytic reaction involves a formal [3 + 3] annulation between enals and substituted malonamides enabling the production of glutarimide derivatives in a single chemical operation via concomitant formation of C−C and C−N bonds. The reaction offers easy access to a broad range of functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Mostly known as convenient, air-stable precursors to N -heterocyclic carbenes (NHCs) used in organocatalytic transformations, 1,2,4-triazolium salts also form upon deprotonation of NHC ligands for transition metal catalysts. Beyond the field of catalysis, these 1,2,4-triazole-based ligands form phosphorescent cyclometalated complexes with the substituents on the carbene ligand being key to their tunable emission wavelengths, while other late transition metal complexes containing 1,2,4-triazole ligands have shown promising in vitro anticancer activity in studies involving breast, colon, lung, skin, liver, and cervical cancer as well as leukemia. N -Aryl-substituted 1,2,4-triazoles are also frequent building blocks in organic compounds with biological activity. Although less common than imidazolium or 1,2,3-triazolium salts, 1,2,4-triazolium salts have been successfully used as ionic liquids for dissolving cellulose …”
Section: Introductionmentioning
confidence: 99%
“…Mostly known as convenient, air-stable precursors to N -heterocyclic carbenes (NHCs) used in organocatalytic transformations, 1,2,4-triazolium salts also form upon deprotonation of NHC ligands for transition metal catalysts. Beyond the field of catalysis, these 1,2,4-triazole-based ligands form phosphorescent cyclometalated complexes with the substituents on the carbene ligand being key to their tunable emission wavelengths, while other late transition metal complexes containing 1,2,4-triazole ligands have shown promising in vitro anticancer activity in studies involving breast, colon, lung, skin, liver, and cervical cancer as well as leukemia. N -Aryl-substituted 1,2,4-triazoles are also frequent building blocks in organic compounds with biological activity. Although less common than imidazolium or 1,2,3-triazolium salts, 1,2,4-triazolium salts have been successfully used as ionic liquids for dissolving cellulose …”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a 2019 article by Porey et al, 24 the reaction of cinnamic aldehyde 8 with aryl-substituted malondiamide 12 in the presence of 10 mol% mesityl-substituted NHC catalysts was studied. They found that product 13 could be obtained with good stereoselectivity (91% ee , dr = 4:1) and 56% yield using DBU and oxidant III in tetrahydrofuran (Scheme 7 ).…”
Section: Michael Additionmentioning
confidence: 99%
“…(Scheme 54). [81] Formation of enolate 46 from the enal-derived α,β-unsaturated acyl azolium via conjugate addition of the enolizable diamide, internal proton transfer/tautomerization and imide formation are salient steps of the postulated organocatalytic cycle.…”
Section: Cà C/cà N Cà N/cà N Cà S/cà N Bond Formation (Michael/lactam...mentioning
confidence: 99%